Revision of the tribe Pogonini (Coleoptera, Carabidae, Trechinae) from the Ibero-Balearic region - Muñoz-Santiago, José; Ortuño, Vicente M. (European Journal of Taxonomy, 2022)
In the Iberian Peninsula and the Balearic Islands, Pogonini (Coleoptera, Carabidae) is the least species-rich tribe of Trechinae. Nevertheless, the taxon is relatively poorly studied in this territory, and the available records are mostly published in old and/or faunistic works. The present study provides a taxonomic revision of the 3 genera and 11 species of Pogonini occurring in the Ibero-Balearic region, with an identification key, diagnoses and illustrations of their external morphology and aedeagus. The chorology of the species was also studied, and was assessed by obtaining precise records from published papers and the collection localities of the examined material. These data were used to make updated distribution maps (with several new occurrence points) that reveal a strong regionalization of the tribe in the Ibero-Balearic territory. The species occur in humid and saline environments, especially along the meridional and Mediterranean coasts of the Iberian Peninsula and in inner arid localities of eastern Spain. This result agrees with the widely accepted halobiont condition of the group. However, sampling bias must be considered, and new records are expected to be provided from future revisions of collections and new samplings.